(untitled) (CAHIERS MAGELLANES-NS, 2024)
Communication skills are vital in medical education as they facilitate effective interactions between healthcare providers and patients. Objectives: To evaluate the effect of flipped classrooms in teaching communication skills to first-phase MBBS students in a medical college in eastern India. Methodology and Participants: This study was carried out among two hundred Phase I MBBS learners after obtaining institutional ethical clearance and informed consent from the participants. Five faculty members of the Department of Physiology acted as facilitators for the sessions. A module was prepared and validated by senior faculty members of the same department. Four interactive face-to-face (two hours each) sessions were conducted for the students and the rest interactions were done using WhatsApp groups. Students were divided into 10 groups with 20 students in each group according to class roll numbers. Results: Assessment of communication skills during the contact sessions was done by facilitators and peers using the Gap-Kalamazoo communication skill assessment form and results showed that the participants performed between fair to very good in all the 9 items. The participants did best in the following three items of the assessment scale: Opens the discussion; Gathers information; Demonstrates empathy. Pre-test score of MCQ exam: 41.35 ± 2.14 vs. Post-test score of MCQ exam: 81.4 ± 4.12; P value: <0.01** (highly significant). Students were satisfied with the knowledge and skills they had acquired and this module motivated them to join similar classes in the future, this is as per responses received in the feedback survey and on analysis of reflections. Conclusions: The learners and participants were satisfied with the method of teaching communication skills using flipped classes in the early phase of the MBBS curriculum. The potential for students to exercise newly acquired skills in a real-world setting was the most favored and the most effective method of teaching-learning communication. Self-reflection consolidated learning success.